Multicultural Society in Digital Comic 304th Study Room (Session 1) - Uli Shafiyati Shafiyati (LPPM Institut Pesantren KH. Abdul Chalim, 2018)
Digital comic or webtoon has its own way of delivering messages to readers, namely using visual and verbal language. Comic can also portray social condition or especially multicultural society where the comic is written. Taking 304th Study Room (Session 1) comic as its object, this study aimed to assess the representation of cultural diversity in the webtoon so it knows what the ideology delivered by the webtoonist. This research is a qualitative research. The theoretical basis in this study is the semiotic theory of Roland Barthes which is seen through the level of its meaning. The results of this study show that through semiotic Roland Barthes the diversity of cultures in the webtoon 304th Study Room (season 1) is represented through characters backgrounds of different etnicity or race and beliefs and characters interaction in the webtoon. The weboonist wants to convey the ideal pluralistic society so that broadly speaking, the myths in the webtoon are cultural diversity, multicultural society. So it can be said that digital comic or webtoon play an important role as a products of popular culture to instilling or perpetuating ideology, especially Pancasilais multicultural society in Indonesia.